Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Given:
[tex]\[
\begin{array}{l}
p: 2x = 16 \\
q: 3x - 4 = 20
\end{array}
\][/tex]

Which is the converse of [tex]\( p \rightarrow q \)[/tex]?

A. If [tex]\( 2x \neq 16 \)[/tex], then [tex]\( 3x - 4 \neq 20 \)[/tex].
B. If [tex]\( 3x - 4 \neq 20 \)[/tex], then [tex]\( 2x \neq 16 \)[/tex].
C. If [tex]\( 2x = 16 \)[/tex], then [tex]\( 3x - 4 = 20 \)[/tex].
D. If [tex]\( 3x - 4 = 20 \)[/tex], then [tex]\( 2x = 16 \)[/tex].


Sagot :

To find the converse of the statement [tex]\( p \rightarrow q \)[/tex], let's first understand what the original statement [tex]\( p \rightarrow q \)[/tex] means:

- [tex]\( p \)[/tex]: [tex]\( 2x = 16 \)[/tex]
- [tex]\( q \)[/tex]: [tex]\( 3x - 4 = 20 \)[/tex]
- [tex]\( p \rightarrow q \)[/tex]: If [tex]\( 2x = 16 \)[/tex], then [tex]\( 3x - 4 = 20 \)[/tex].

The converse of [tex]\( p \rightarrow q \)[/tex] is [tex]\( q \rightarrow p \)[/tex]. This means that if [tex]\( q \)[/tex] is true, then [tex]\( p \)[/tex] must also be true.

Let's now rewrite this in logical statements:

- [tex]\( q \rightarrow p \)[/tex]: If [tex]\( 3x - 4 = 20 \)[/tex], then [tex]\( 2x = 16 \)[/tex].

We can thus match this with the given answer choices:

1. If [tex]\( 2x \neq 16 \)[/tex], then [tex]\( 3x - 4 \neq 20 \)[/tex].
2. If [tex]\( 3x - 4 \neq 20 \)[/tex], then [tex]\( 2x \neq 16 \)[/tex].
3. If [tex]\( 2x = 16 \)[/tex], then [tex]\( 3x - 4 = 20 \)[/tex].
4. If [tex]\( 3x - 4 = 20 \)[/tex], then [tex]\( 2x = 16 \)[/tex].

The correct converse of [tex]\( p \rightarrow q \)[/tex] is represented by:

If [tex]\( 3x - 4 = 20 \)[/tex], then [tex]\( 2x = 16 \)[/tex].

So, choice (4) is the correct answer.